P.S. - Grace, Topher; Rudd, Paul.; Byrne, Gabriel; Harden, Marcia Gay.; Linney, Laura; Kessel, Robert ([S.l.] : Sony Pictures Home Entertainment, 2005)
Laura Linney and Topher Grace shine in this bittersweet tale of losing love and finding it again. When divorced, thirty-something Columbia University admissions officer Louise Harrington meets one of the school's young applicants, she is floored by his uncanny resemblance to her deceased high school sweetheart - and haunted by the notion that he may be her love reincarnated.